2005
DOI: 10.3758/bf03196772
|View full text |Cite
|
Sign up to set email alerts
|

Working memory span tasks: A methodological review and user’s guide

Abstract: Working memory (WM) span tasks-and in particular, counting span, operation span, and reading span tasks-are widely used measures of WM capacity. Despite their popularity, however, there has never been a comprehensive analysis of the merits of WM span tasks as measurement tools. Here, we review the genesis of these tasks and discuss how and why they came to be so influential. In so doing, we address the reliability and validity of the tasks, and we consider more technical aspects of the tasks, such as optimal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

33
2,231
5
29

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 2,257 publications
(2,298 citation statements)
references
References 104 publications
(144 reference statements)
33
2,231
5
29
Order By: Relevance
“…We chose the complex span paradigm, which is a well-established measure of WM capacity (cf. Conway et al, 2005), as well as an excellent predictor for reasoning (e.g., Engle, Tuholski, Laughlin, & Conway, 1999;Süß, Oberauer, Wittmann, Wilhelm, & Schulze, 2002). Moreover, in our recent study mentioned above , we found that training with complex span tasks was more effective than training with other tasks of WM capacity in terms of transfer to untrained WM and reasoning tasks.…”
Section: Introductionsupporting
confidence: 49%
See 2 more Smart Citations
“…We chose the complex span paradigm, which is a well-established measure of WM capacity (cf. Conway et al, 2005), as well as an excellent predictor for reasoning (e.g., Engle, Tuholski, Laughlin, & Conway, 1999;Süß, Oberauer, Wittmann, Wilhelm, & Schulze, 2002). Moreover, in our recent study mentioned above , we found that training with complex span tasks was more effective than training with other tasks of WM capacity in terms of transfer to untrained WM and reasoning tasks.…”
Section: Introductionsupporting
confidence: 49%
“…Modeled after the storage and processing training intervention in an earlier study , WM training consisted of three complex span tasks (Conway, et al, 2005;Daneman & Carpenter, 1980) with varying material (numerical, verbal, and figural-spatial). In these tasks, the presentation of memoranda (each for 1 s) alternates with a secondary distractor task, in which participants have to make a decision as quickly and as accurately as possible.…”
Section: Wm Training Tasksmentioning
confidence: 99%
See 1 more Smart Citation
“…The tasks were taken from Unsworth et al (2009) and translated into German. We measured working memory capacity using the partial credit score (the sum of all items recalled in the correct position over all trials) as the dependent variable (Conway et al, 2005).…”
Section: Automated Working Memory Span Tasksmentioning
confidence: 99%
“…This combination of short-term storage and processing requirements implements the basic definition of WM as simultaneous storage and processing (Baddeley, 2007). Because of potential trade-offs between the two components, CSTs come with the problem that performance on the secondary task cannot easily be disregarded when determining WM span on the basis of number of items recalled (Conway et al, 2005).…”
mentioning
confidence: 99%